Lipid‐soluble fraction of Shakuyaku‐kanzo‐to inhibits myometrial contraction in pregnant women. Issue 5 (25th November 2014) - Sumi, Genichiro; Yasuda, Katsuhiko; Tsuji, Shoko; Kanamori, Chiharu; Tsuzuki, Tomoko; Cho, Hisayuu; Nishigaki, Akemi; Okada, Hidetaka; Kanzaki, Hideharu
Abstract Aim Shakuyaku‐kanzo‐to, a Kampo medicine composed equally of shakuyaku and kanzo, is an antispasmodic drug that can inhibit contraction of uterine smooth muscles in pregnant women and rats. We aimed to test the inhibitory effects of water‐ and lipid‐soluble extracts of shakuyaku‐kanzo‐to, shakuyaku, and kanzo in order to identify the fraction responsible for inhibiting uterine smooth muscle contraction in pregnancy. Material and Methods Myometrial tissues were obtained from pregnant women and rats. The water‐ and lipid‐soluble fractions of shakuyaku‐kanzo‐to, shakuyaku, and kanzo were obtained using the method of Bligh and Dyer. Lipid‐soluble fractions were also partially purified using thin‐layer chromatography (TLC) with a chloroform : methanol : water (65:25:4 by volume) solvent system to yield four TLC fractions. The effect of each fraction on oxytocin‐induced myometrial contraction was examined in vitro. Results Lipid‐soluble fractions obtained from shakuyaku‐kanzo‐to and kanzo inhibited myometrial contraction; water‐soluble fractions had no effect. Of the four TLC fractions, the inhibitory effect was greatest with TLC fraction 1 (0.75 < Rf value ≤ 1.0). Neither the water‐soluble nor the lipid‐soluble fraction from shakuyaku inhibited myometrial contraction. Conclusions These results suggest that lipid‐soluble substances with low polarity derived from kanzo are responsible for the inhibitory effect of shakuyaku‐kanzo‐to on myometrial contraction.